Plasma metabolite biomarkers predictive of radiation induced cardiotoxicity. (November 2020) - Unger, Keith; Li, Yaoxiang; Yeh, Celine; Barac, Ana; Srichai, Monvadi B; Ballew, Elizabeth A; Girgis, Michael; Jayatilake, Meth; Sridharan, Vijayalakshmi; Boerma, Marjan; Cheema, Amrita K
Highlights: Metabolomics biomarkers predictive of Radiation-induced heart disease (RIHD). Use of rat model and patient plasma to assess overlap in radiation response. Predictive biomarkers of adverse cardiac function outcomes in esophageal cancer. Abstract: Purpose: Although advancements in cancer treatments using radiation therapy (RT) have led to improved outcomes, radiation-induced heart disease (RIHD) remains a significant source of morbidity and mortality in survivors of cancers in the chest. Currently, there are no diagnostic tests in clinical use due to a lack of understanding of the natural history and mechanisms of RIHD development. Few studies have examined the utility of using metabolomics to prospectively identify cancer survivors who are at risk of developing cardiotoxicity. Methods: We analyzed plasma and left ventricle heart tissue samples collected from a cohort of male Sprague Dawley (SD) rats that were either sham irradiated or received fractionated doses (9 Gy per day × 5 days) of targeted X-ray radiation to the heart. Metabolomic and lipidomic analyses were utilized as a correlative approach for delineation of novel biomarkers associated with radiation-induced cardiac toxicity. Additionally, we used high-resolution mass spectrometry to examine the metabolomic profiles of plasma samples obtained from patients receiving high dose thoracic RT for esophageal cancer. Results: Metabolic alterations in the rat model and patient plasma profiles, showed commonalities of radiation response that included steroid hormone biosynthesis and vitamin E metabolism. Alterations in patient plasma profiles were used to develop classification algorithms predictive of patients at risk of developing RIHD. Conclusion: Herein, we report the feasibility of developing a metabolomics-based biomarker panel that is associated with adverse outcomes of cardiac function in patients who received RT for the treatment of esophageal cancer.